(x+4)+(x+5)+(x+5)=2

Simple and best practice solution for (x+4)+(x+5)+(x+5)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)+(x+5)+(x+5)=2 equation:


Simplifying
(x + 4) + (x + 5) + (x + 5) = 2

Reorder the terms:
(4 + x) + (x + 5) + (x + 5) = 2

Remove parenthesis around (4 + x)
4 + x + (x + 5) + (x + 5) = 2

Reorder the terms:
4 + x + (5 + x) + (x + 5) = 2

Remove parenthesis around (5 + x)
4 + x + 5 + x + (x + 5) = 2

Reorder the terms:
4 + x + 5 + x + (5 + x) = 2

Remove parenthesis around (5 + x)
4 + x + 5 + x + 5 + x = 2

Reorder the terms:
4 + 5 + 5 + x + x + x = 2

Combine like terms: 4 + 5 = 9
9 + 5 + x + x + x = 2

Combine like terms: 9 + 5 = 14
14 + x + x + x = 2

Combine like terms: x + x = 2x
14 + 2x + x = 2

Combine like terms: 2x + x = 3x
14 + 3x = 2

Solving
14 + 3x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 3x = 2 + -14

Combine like terms: 14 + -14 = 0
0 + 3x = 2 + -14
3x = 2 + -14

Combine like terms: 2 + -14 = -12
3x = -12

Divide each side by '3'.
x = -4

Simplifying
x = -4

See similar equations:

| -16x^2=1 | | 12x-6=12+15x | | 42=7[z-3] | | (x+4)(x+1)(x-(3+i))(x-(3-i))=0 | | 2x^2-1=-163 | | 8y-6y=20 | | 13=9t-14 | | (8x+7)(x+1)=9 | | 16x^2+24ax+8y^2=0 | | 14g-13g=7 | | X*-1=24 | | 2y(y-1)+6y=-10 | | 9/4-3/4= | | F(-3)=3x+7 | | y=6kx-2 | | 9(2+(-14))-4(-14)=3(-14)-10 | | 8x^2+24ax+8y^2=0 | | 15x-9x^2=0 | | 15x-9x^2=0 | | 8x^2+24ax+8y^2=0 | | (14-2x)=(12x+4) | | -50+5x+x^2=48 | | 6-5x=15x-34 | | -6x=-150 | | -8+2-6r-7huser=8 | | 3x^3-25x^2-50x=0 | | 3x^3-25x^2-50x=0 | | 7x-.25=15 | | 20=5-3u | | 2r^2=-4+14 | | -2(w+9)=2 | | 5b-b=400 |

Equations solver categories